Scaling of musculoskeletal models using open-chain isokinetic test data and optimization - Enqvist, J.; Czarnowski, J.; Arndt, A.; Holmberg, J. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Musculoskeletal modeling offers a unique possibility to predict the internal loading acting on joint-muscle structures during sport-specific movements in winter sports, e.g. cross-country skiing and alpine skiing 1-4. To accurately represent any individual, a musculoskeletal model`s anthropometry and muscle strength must be scaled. Parameters that govern muscle strength are highly subject specific which affects the accuracy of predicted internal loading. The standard anthropometric scaling method (LMS) may be sufficient for the general population, but better accuracy is required for elite athletes due to large muscle structure deviations. We propose a method for scaling subject-specific muscle parameters.